EFFECT OF BARIATRIC SURGERY ON QUALITY OF LIFE IN OBESE PATIENTS: A GLOBAL SYSTEMATIC REVIEW: EFECTO DE LA CIRUGÍA BARIÁTRICA SOBRE CALIDAD DE VIDA EN OBESOS: UNA REVISIÓN SISTEMÁTICA GLOBAL. - López Espinoza, Miguel Ángel (2024)
In a situation of obesity and when treatment goals are not met, bariatric surgery can be a promising alternative; with effects at the physical level as well as at the psychological level of the quality of life. This study aims to determine the effect of bariatric surgery on the quality of life in obese men and women between 20 and 60 years of age. A Systematic Review (SR) was carried out with meta-analysis of randomized systematic reviews, which compare the quality of life in patients after bariatric surgery. Electronic databases were consulted: Ebsco, Scopus, Pubmed and Cochrane Library. The response variables were: physical, social, mental and emotional function. They were submitted to meta-analysis, with R 4.2.2. Three SRs were included, of which 25 clinical trials were combined with 3-6 and 12-month follow-up after bariatric surgery, finding statistically significant changes in physical function scores (1.20; 95% CI: 0.80-1 .61), social (0.95; 95% CI: 0.66-1.25), mental (0.35; 95% CI: -0.21- +0.90) and emotional (0.54; 95% CI: 0.03-1.06). The surroundings of the quality of life improve post bariatric surgery in obese patients.